The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ra01296a
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanosheet-assisted immobilization of Ag nanoparticles on graphene/Ni foam for highly efficient reduction of 4-nitrophenol

Abstract: ZnO nanosheet-assisted immobilization of Ag nanoparticles on graphene/Ni foam forming a novel hybrid structure for catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For example, ZnO-MWCNT interaction promotes the hydrophilic character of the sample meanwhile Ag remains highly dispersed and capped into the sponge-like morphology of ZnO. Some authors had reported that the presence of carbonaceous components interacting with the support prevents the leaching of Ag nanoparticles during the reaction [81] and promotes the exceptional speed for the electron transfer between Ag and C [26]. In addition, it has been found that the presence of ZnO acts as a homogenizer and stabilizer for Ag nanoparticles on carbonaceous hybrid surfaces (Gr/NiF) because of its assisted role in carrying and immobilizing the Ag nanoparticles to the surface via chelation and complexation of surfactant molecules during the in situ reduction process of Ag ions [26].…”
Section: Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, ZnO-MWCNT interaction promotes the hydrophilic character of the sample meanwhile Ag remains highly dispersed and capped into the sponge-like morphology of ZnO. Some authors had reported that the presence of carbonaceous components interacting with the support prevents the leaching of Ag nanoparticles during the reaction [81] and promotes the exceptional speed for the electron transfer between Ag and C [26]. In addition, it has been found that the presence of ZnO acts as a homogenizer and stabilizer for Ag nanoparticles on carbonaceous hybrid surfaces (Gr/NiF) because of its assisted role in carrying and immobilizing the Ag nanoparticles to the surface via chelation and complexation of surfactant molecules during the in situ reduction process of Ag ions [26].…”
Section: Catalytic Performancementioning
confidence: 99%
“…However, the modification of ZnO nanostructures by Ag nanoparticles improves their catalytic activity in the reduction of 4-nitrophenol due to the electron transfer promotion by the Ag metallic species despite the Ag nanoparticles agglomeration [23][24][25]. To reduce the effect of Ag nanoparticles agglomeration, Liu et al proposed a novel hybrid nanomaterial composed of Ag nanoparticles, ZnO nanosheets, graphene and nickel foam, Ag/ZnO/Gr/NiF [26]. The obtained composite synthesized via a complex procedure (chemical vapor deposition, hydrothermal treatment and chemical reduction) was characterized with high catalytic activity and stability for the reduction of 4-nitrophenol to 4-aminophenol.…”
Section: Introductionmentioning
confidence: 99%